Seaweeds as sustainable alternative for enhancing agriculture - Akil, M; Gomathy, M; Sabarinathan, K G; Sujatha, K; Baskar, K (Plant Science Today, 2025)
The existing dominance of chemical inputs in agriculture has pushed the invaluable soil resource to its brink. The adoption of high yielding varieties by farmers worldwide has demanded the use of chemical fertilizers and plant protection agents. While these practices have played a crucial role in achieving food security, they have also given rise to rather serious complications, including the deterioration of soil health, the presence of chemical residues in agricultural produce and environmental pollution. This has necessitated the formulation of efficient alternative inputs that help agriculturists to achieve ample crop yields while ensuring the sustenance of soil health and productivity. The vast sea of seaweeds is an excellent candidate that suits best for the current scenario, being a wholesome provider for plant health and productivity. The presence of plant growth regulators and several bioactive compounds that can stimulate vigorous plant growth, elicit plant defense mechanisms against biotic and abiotic stressors and enhance yield are some of the promising reasons which make seaweeds a suitable biostimulant for crop production. This review is an attempt to enrich the existing knowledge on seaweeds by exploring the agricultural benefits of seaweeds and elucidating the underlying mechanisms through which these benefits are realized.